anyone please solve this problem
Attachments:
![](https://hi-static.z-dn.net/files/d49/326440fca1f089df1e1456464d3eaa99.jpg)
Answers
Answered by
7
Given :
To Show :
Assuming ,
⟶
⟶
➳ ...... [ 1 st ]
➳ ...... [ 2 nd ]
➳ ...... [ 3 rd ]
Subtracting ( 2 - 1 ) , ( 3 - 2 ) , ( 1 - 3 ) , We get :
➳ =
➳ =
➳ =
⟹
⟹
⟹
⟹
So, It's Done !!
Answered by
10
Answer:
are u ok? or what happens? siso? thank you for your answer that you have given it was the correct one . be happy
Similar questions
Social Sciences,
4 months ago
Social Sciences,
4 months ago
Math,
8 months ago
Math,
8 months ago
Physics,
1 year ago